Eletrocardiografia, sedação e qualidade da recuperação do butorfanol ou buprenorfina em cães pré-tratados pela acepromazina - Santos, Paulo Sergio Patto dos [UNESP] (2010)
The aim of this work was to evaluate the electrocardiography effects (ECG), sedation time and quality of recovery due to buprenorphine (G1) and butorphanol (G2) administration in dogs pretreated with acepromazine. Seven adult dogs were submitted to both protocols, with a thirty days interval between groups. G1 animals were premedicated with acepromazine (0.1 mg/kg) followed 10 minutes later with buprenorphine (0.005 mg/kg), both applied intravenously. The same procedure was performed for G2 employing butorphanol (0.3 mg/kg) instead of buprenorphine. The measurements of the variables heart rate (HR), duration and amplitude of P wave, P-R intervals (PR), QRS complex duration, R wave amplitude, Q-T intervals (QT) and R-R intervals (RR) were taken immediately before application of acepromazine (M0), 10 minute after administration of acepromazine (M10) and 10 minutes after opioids administration (M20). Serial measurements were carried out in 10 minute intervals after the administration of butorphanol or buprenorphine up to 60 minutes. Numeric data were submitted to Tukey Analysis (p < 0.05). The amplitude of P wave decreased 30 minutes after the administration of the butorphanol. Sedation time was longer in G1 (78 minutes) than G2 (72 minutes) and recovery was good in both groups. These results indicate that butorphanol or buprenorphine produced discreet alterations on ECG, which don´t contraindicate its clinical use.